Environmental Journalists Perspective on the Coverage of Environmental Issues in Media of Pakistan - Ahmed, Masroor; Minhas, Dr Shahid; Hussain, Dr Tasaddaq (Journal of Peace, Development and Communication, 2020)
Pakistan is facing serious environmental issues which is becoming a risk for the citizens of the country. This study is designed to focus on the Environmental journalist’s perspective on the coverage of environmental issues in the Media of Pakistan. Survey research method was used and a structured questionnaire was distributed to collect data from environmental journalists in Pakistan. A non-probability sampling method, snow ball sampling was applied to collect data from the journalists on the specified issues. The questionnaire was sent to 20 journalists covering environmental beats, in which 18 responded. All major issues prevailing in the context of environment (globally/locally) were incorporated in the questionnaire. The results showed that, according to the environmental journalists, the coverage of environmental issues in the media of Pakistan is not satisfactory, even considerable low, print and electronic media were the only major channel of communications that covered environmental issues, while these issues have significance and also audiences have some sort of interest in these issues, but journalists noted that there is no such options to highlight in the media due to some major reasons except a little coverage in the media.